GREEN ECONOMICS: A SUSTAINABLE APPROACH TO ECONOMIC DEVELOPMENT - Dr. M. Rajeswari (International Conference on Health Science, Green Economics, Educational Review and Technology, 2019)
Abstract Green economics is an emerging field that integrates environmental sustainability with economic theory and practice. This research paper aims to explore the concept of green economics, its principles, and its potential for fostering sustainable development. The paper begins by providing an overview of the current environmental challenges facing the world and the need for a paradigm shift in economic thinking. It then delves into the key principles and pillars of green economics, including the valuation of natural resources, the promotion of renewable energy, sustainable consumption and production patterns, and the pursuit of social equity. The paper also examines the role of green economics in policy-making and the potential economic benefits it can generate. Finally, the challenges and potential criticisms of green economics are discussed, along with recommendations for future research and implementation